Happiness research for public policy and administration - Okulicz-Kozaryn, Adam (Transforming government, 2016)
Purpose The purpose of this viewpoint is to introduce happiness research for public policy and administration scholars and practitioners. It focuses on what can be useful for the discipline, provides relevant examples and presents the most recent findings and directions for future research. Design/methodology/approach This paper is a combination of literature review, argumentation and illustrations. Findings Over the past few decades, there has been a tremendous growth in happiness research, and over the past few years, this research has started addressing policy issues such as housing, transportation and inequality. Strikingly, public policy and administration discipline has failed to notice these developments. Happiness research has great potential, and it can be used in many theoretical and practical ways to advance the common good. Originality/value Happiness is extremely important and useful for public policy and administration and yet largely overlooked in the discipline. Existing literature reviews are not written with the discipline in mind, and this viewpoint is aimed at filling this gap.